2020
DOI: 10.1186/s13012-020-01038-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparing effects of two higher intensity feedback interventions with simple feedback on improving staff communication in nursing homes—the INFORM cluster-randomized controlled trial

Abstract: Background Effective communication among interdisciplinary healthcare teams is essential for quality healthcare, especially in nursing homes (NHs). Care aides provide most direct care in NHs, yet are rarely included in formal communications about resident care (e.g., change of shift reports, family conferences). Audit and feedback is a potentially effective improvement intervention. This study compares the effect of simple and two higher intensity levels of feedback based on goal-setting theory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…The main trial results showed a statistically significant increase in care aides' involvement in formal team communications about resident care in both the basic and enhanced assisted feedback arms compared to the Simple Feedback arm. However, no differences were observed between the basic and enhanced-assisted feedback arms [12].…”
Section: The Inform Studymentioning
confidence: 77%
See 2 more Smart Citations
“…The main trial results showed a statistically significant increase in care aides' involvement in formal team communications about resident care in both the basic and enhanced assisted feedback arms compared to the Simple Feedback arm. However, no differences were observed between the basic and enhanced-assisted feedback arms [12].…”
Section: The Inform Studymentioning
confidence: 77%
“…Study arms had few differences in the extent of fidelity delivery, receipt, and enactment. This helps us understand IN-FORM trial results: basic-and enhanced-assisted feedback arms had significantly higher follow-up team communication scores than the simple feedback arm, but the two assisted feedback arms did not differ in scores [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While care aide involvement in formal team communications about resident care was our primary study outcome, INFORM is designed to be tailorable to address any of a wide variety of possible outcomes (e.g., care staff quality of work-life, leadership practices, or resident outcomes). We published the methods of INFORM in a trial protocol [ 13 ] and subsequently published results on INFORM’s effectiveness [ 14 ] and the impact of intervention fidelity on intervention effectiveness [ 15 ]. This study addresses an important additional aim outlined in our trial protocol [ 13 ]: to assess longer-term effects of INFORM.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed [ 14 ] that care aide involvement in formal communications about resident care at follow up was 0.17 points higher in both the basic (95% confidence interval [CI]: 0.03; 0.32, p = 0.021) and enhanced study arms (95% CI 0.01; 0.33, p = 0.035), compared to simple feedback—with no differences between the study arms with the highest (enhanced) and mid-level (basic) intensity. Intervention fidelity was moderate to high, and higher fidelity enactment was associated with larger improvements in formal team communications [ 15 ].…”
Section: Introductionmentioning
confidence: 99%